Analisa UI dalam Perancangan Aplikasi Ekspor Hasil Laut “FishGo!” dengan Metode SUS - Nanda, Ketut Agus Cahyadi; Suputra, I Putu Gede Hendra (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 3 (2023): JNATIA Vol. 1, No. 3, Mei 2023, 2023)
This research discusses the development of the Fish Go! application, which aims to facilitate fishermen in finding market opportunities, particularly within the business sector. The author identifies several challenges faced by fishermen in terms of marketing and selling their catch. Additionally, there are opportunities to meet the demand for marine products in the tourism sector in Indonesia. The Fish Go! The application seeks to integrate fishermen and the business sector into a single digital platform, with the goal of expanding the fishermen's market reach and providing convenience for buyers in obtaining fresh and high-quality seafood. This research involves a literature study to gain a deeper understanding of application interface analysis and usability in general. The User Journey Map method is used to identify the problems faced by potential users of the Fish Go! application. The usability testing phase was conducted using the System Usability Scale (SUS) method, involving the distribution of questionnaires to 20 respondents. The quantitative data obtained from the SUS scores indicate that the Fish Go! the application has a good level of usability and is suitable for further development, with an average SUS score of 84, exceeding the average threshold for usability testing. The results of this research show that the Fish Go! this application has the potential to support partnerships between fishermen and the business sector in utilizing marine resources in Indonesia. By leveraging technology and digital platforms, it is expected to improve efficiency and provide broader market opportunities for fishermen, while also meeting the demand of the business sector for fresh and high-quality seafood.